Estimating a block cave yield zone shape using comprehensive microseismic data - Birch, D.J.; Meyer, S.G.; Sanker Pararath, G.; Pilkington, J.; Orrego, C.; Osorio, A.; Haayat, H. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Estimating the shape of a developing cave remains an integral part of block cave mining. A growing cave perturbs the in situ stress field and induces seismic events, which in turn carry with them valuable information that can be used to formulate a more complete geomechanical model of the mine. Constraining the evolution of the yield zone has implications for forecasting the seismic hazard and improving the ability of numerical models to predict instabilities. The utility of microseismic data is limited by sensor array characteristics and overall quality of data processing. As a result, case studies often present interpretations based on a subset of available methods, from basic locations of event hypocentres to more advanced tomographic imaging using body wave travel times. This paper presents a unified, balanced framework using multiple sources of information derived from microseismic data to provide a comprehensive estimate of the yield zone around an Australian block cave mine with high-quality seismic data. The result is compared to other measurements such as cave tracking beacons and open holes.